Forecasting Your Future: Nutrition Matters Curriculum with Teacher Training Promotes Students to Try New Fruits and Vegetables. Issue 7 (3rd June 2020) - Kaschalk-Woods, Elizabeth; Fly, Alyce D; Foland, Elizabeth B; Dickinson, Stephanie L; Chen, Xiwei
ABSTRACT: Background: Many high school students do not consume the recommended amounts of fruits and vegetables. Objective: This study evaluated student outcomes from a new nutrition curriculum that includes messages from the 2015–2020 Dietary Guidelines for Americans with a teacher training component for high school Family and Consumer Sciences (FACS) teachers. Methods: A cluster-randomized controlled study was conducted with 1104 students in FACS classes from 35 schools, taught by teachers trained in implementing a new curriculum (intervention) and teachers using their usual curricula (control). Students completed online surveys at the beginning and end of the semester, that is, pre- and postexposure to the nutrition curricula. Intention-to-treat analyses as hierarchical linear modeling were performed to determine if the intervention students had significant changes compared with the control students for knowledge of nutrition concepts, familiarity of, preferences for, affinity toward, number of times trying new, and daily times eating fruits and vegetables. Per-protocol analyses used the same hierarchical linear model but instead of control and intervention groups, students were split into 3 levels describing the amount of the new curriculum they received (0%, 1–50%, and 51–100%). Results: Students exposed to 51–100% of the new curriculum tried more fruits and vegetables than both the control students and the students that received 1–50% of the curriculum ( P = 0.009 for fruits and P = 0.002 for vegetables). Additionally, there were higher increases in the number of times intervention students tried a new fruit ( P = 0.027) and vegetable ( P = 0.022) compared with the control students, regardless of the amount of curriculum received. Conclusions: Our findings show that the curriculum, Forecasting Your Future: Nutrition Matters, has promise for increasing exposure to new fruits and vegetables for students. If teachers use most of the curriculum, students are likely to try more new fruit and vegetables, which could ultimately contribute to improved health.